Digitalisasi Pemerintahan EFEKTIVITAS SISTEM PERIZINAN ONLINE DALAM PENINGKATAN PELAYANAN PUBLIK DI KABUPATEN LEBAK - MT Harsana (NIAGARA Scientific Journal, 2023)
The implementation of the online licensing system is one of the technology and information-based services that is expected by the community to facilitate access to public services, especially licensing and for investors in obtaining public services. Online licensing is a new thing that is applied in providing licensing services in the Lebak Regency Government, where the community is accustomed to direct and offline services. One of the impacts after online licensing was implemented effectively in 2018 was a very significant decrease in the number of license issuances compared to pre-online services. This writing aims to analyze the effectiveness of the online licensing system at the One-Stop Investment and Integrated Service Office (DPMPTSP) of Lebak Regency. A qualitative method with a descriptive approach is used in this writing to analyze the effectiveness of the online licensing system. The informants in this writing are officials, staff and people who make licenses online. Based on the results of the analysis conducted, the Online Licensing System at DPMPTSP Lebak Regency has not been effective. The dimensions used to measure effectiveness are goal achievement, integration and adaptation. Only the adaptation dimension has been achieved while the achievement of goals and integration has not been achieved. The steps and actions of DPMPTSP Lebak Regency so that the online licensing system can be effective are reducing system errors in the online licensing system by continuously developing the system. Making the online licensing system more understandable and increasing dissemination regarding the online licensing system through various media both print and electronic as well as direct socialization to the community.